Evaluación del uso de insecticidas en el control de spodoptera frugiperda j. e. smith. en zea mays l., en Huacapongo – La Libertad - Salinas Delgado, Linder (2017)
The present research work called "evaluation of the use of insecticides to control Spodoptera frugiperda J. E. Smith in Zea mays l.", took place in Huacapongo - La Libertad. The objective of this study was to evaluate and describe the use of insecticides to control Spodoptera frugiperda J. E. Smith in Zea mays l. in the fields of farmers who sow as a main crop maize. The parameters evaluated were: insecticides used, frequency of application, application rate, number of applications, preparation of mixtures, chemical control costs, production costs, performance, among others. The data were obtained through the application of a survey. As a result of this study, it is concluded that farmers in Huacapongo, each year increase the number of insecticide applications; as well as the dose, increasing the costs of control and hence production costs; due to the scarce information about the rotation of active ingredients or chemical groups that can interfere with the life cycle of the pest and avoid to generate resistance. It is also concluded that each year the corn crop yields decrease by little success controlling the Spodoptera frugiperda J. E. Smith.